How does organizational resilience promote firm growth? The mediating role of strategic change and managerial myopia - Liang, Lin; Li, Yan (Journal of business research, 2024)
•Clarifying the relationship between organizational resilience and firm growth.•Strategic change mediates the link of organizational resilience and firm growth.•Managerial myopia mediates the link of organizational resilience and firm growth.•Environmental uncertainty moderates the link of organizational resilience and behavior. Combining dynamic capability theory and the “capability-behavior-result” research logic, this study sheds light on the influence of organizational resilience on firm growth and how strategic change and managerial myopia mediate this relationship. Furthermore, the moderating role of environmental uncertainty is discussed. We employ a sample of A-share listed manufacturing companies in China during the period 2010–2020. The results demonstrate that organizational resilience promotes firm growth. Strategic change and managerial myopia play a mediating role between organizational resilience and firm growth. Environmental uncertainty positively moderates the relationship between organizational resilience and strategic change, but negatively moderates the relationship between organizational resilience and managerial myopia. Additionally, our findings indicate that the promotion effect of organizational resilience on firm growth is more significant in non-state-owned enterprises, small and medium-sized enterprises, and non-labor-intensive industries. This study offers practical implications for managers seeking sustainable development through organizational resilience.